Geografia Política e Geopolítica Brasileira no século XXI - Gutemberg de Vilhena Silva; Hervé Théry (L'Espace Politique, 2017)
Introductory article of the issue 31 (2017-2) of the journal L’Espace politique entitled "Brazilian political geography and geopolitical in the 21st century".